Adenosine A2A receptor as a potential regulator of Mycobacterium leprae survival mechanisms: new insights into leprosy neural damage - dos Santos, Plinio Marcos Freire; Díaz Acosta, Chyntia Carolina; Rosa, Thabatta Leal Silveira Andrezo; Ishiba, Michelle Harumi; Dias, André Alves; Pereira, Antonio Marcos Rodrigues; Gutierres, Luísa Domingos; Pereira, Melissa Pontes; da Silva Rocha, Matheus; Rosa, Patrícia Sammarco; Bertoluci, Daniele F. F.; Meyer-Fernandes, José Roberto; et al. (Frontiers in Pharmacology, 2024)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae, which can lead to a disabling neurodegenerative condition. M. leprae preferentially infects skin macrophages and Schwann cells -glial cells of the peripheral nervous system. The infection modifies host cell lipid metabolism, subverting it in favor of the formation of cholesterol-rich lipid droplets (LD), that are essential for bacterial survival. Although researchers have made progress in understanding leprosy pathogenesis, many aspects of the molecular and cellular mechanisms of host-pathogen interaction still require clarification. The purinergic system utilizes extracellular ATP and adenosine as critical signaling molecules and plays several roles in pathophysiological processes. Furthermore, nucleoside surface receptors such as the adenosine receptor A2aR involved in neuroimmune response, lipid metabolism, and neuron-glia interaction are targets for treatment of different diseases. Despite the importance of this system, nothing has been described about its role in leprosy, particularly the adenosinergic signaling (AdoS), during M. leprae-Schwann cell interaction.Methods: M. leprae was purified from the hind footpad of athymic nu/nu mice. ST88-14 human cells were infected with M. leprae in the presence or not of specific agonists or antagonists of AdoS. Enzymatic activity assays, fluorescence microscopy, Western blotting and RT-qPCR analysis were performed. M. leprae viability was investigated by RT-qPCR and cytokines were evaluated by ELISA.We demonstrated that M. leprae-infected Schwann cells upregulated CD73 and ADA and downregulated A2aR expression and the phosphorylation of the transcription factor CREB (p-CREB). On the other hand, activation of A2aR with its selective agonist, CGS21680, resulted in: (i) reduced LD accumulation and pro-lipogenic genes expression; (ii) reduced production of IL-6 and IL-8; (iii) reduced intracellular M. leprae viability; and (iv) increased levels of p-CREB.These findings suggest the involvement of the AdoS in leprosy neuropathogenesis, and support the idea that M. leprae, by downmodulating the expression and activity of A2aR in Schwann cells, decreases A2aR downstream signaling, contributing to the maintenance of LD accumulation and intracellular viability of the bacillus.